“Geographies” of primary healthcare access for older adults in the Lisbon Metropolitan Area, Portugal – a territory of differences - Costa, Eduarda Marques da; Costa, Nuno Marques da; Louro, Ana; Barata, Marcela (Saúde e Sociedade, 2020)
Several authors have reflected upon access to health services considering several dimensions, such as availability and accessibility. Due to the aging of societies, the older population’s demands for healthcare increase, and accessibility to these units acquires special importance. Our study aims to characterize the access of older people to healthcare services, facing the possibilities arising from service supply and demand patters. From the supply and demand confrontation, comes the possibility of identifying intraregional dynamics and associating them with the various socioeconomic conditions of older people, family background, modes of transportation, and type of service. This approach considers two methodological phases: calculating the potential for primary healthcare coverage, considering physical accessibility for pedestrian and highway modes; and confronting these values with services demand, determined from surveys conducted with residents. We concluded that, although healthcare centers were designed as a proximity service, service provision, socioeconomic aspects, and the urbanization model entail meaningful inequalities of access in the context of the Lisbon Metropolitan Area.